Singularities of Affine Schubert Varieties - Kuttler, J.; Lakshmibai, V. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
This paper studies the singularities of affine Schubert varieties in the affine Grassmannian (of type Al⁽¹⁾). For two classes of affine Schubert varieties, we determine the singular loci; and for one class, we also determine explicitly the tangent spaces at singular points. For a general affine Schubert variety, we give partial results on the singular locus.